KDRT Ringan Harus Menjadi Delik Biasa: Analisis Yuridis dan Sosiologis UU PKDRT - Muhammad Rezfah Omar (Rechtsregel : Jurnal Ilmu Hukum, 2025)
Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law) classifies several domestic violence crimes, including minor ones, as complaint-based offenses as stipulated in Articles 51, 52, and 53. In practice, this classification often hinders the legal process due to the reliance on complaints from victims, who are often under pressure or threats, or due to the societal stigma that considers domestic violence a private matter. The Minister of Women's Empowerment and Child Protection (PPPA), Arifah Fauzi, stated in Press Release Number: B-257/SETMEN/HM.02.08/05/2025: "Protection and services for victims are still not optimally implemented because only a small proportion of victims are registered in the service system. This condition is suspected to be because many women and children who are victims of violence still do not feel safe to report it." This normative-juridical research aims to analyze the urgency of changing the status of minor domestic violence to a regular crime, so that the prosecution process can be carried out without waiting for an official complaint from the victim. Secondary data, including legal literature and case studies, were used to evaluate the effectiveness of the current Domestic Violence Law. The results indicate that changing the offense from a complaint to a regular offense will provide stronger legal certainty, optimal protection for victims, and a deterrent effect for perpetrators, considering the nature of domestic violence as a public issue, not just a private one.